An Interview with Raja Shehadeh: Documenting the Ordinary in an Unordinary Place. Issue 1 (2nd January 2023) - Alasah, Eman
Abstract: This interview is part of an ongoing PhD research project on contemporary Anglophone Palestinian memoirs, autobiographies, and life narratives. The project examines the linguistic, aesthetic, and thematic elements of a number of texts that document daily life under occupation in Palestine within a settler-colonial theoretical framework. Interviews with authors have been conducted to foreground the textual analysis of the texts. Due to COVID-19 restrictions, this interview was conducted online via Zoom in February 2022, and was later edited by the interviewer and the interviewee.